2016
DOI: 10.4137/jen.s32837
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of TRPA and TRPV Channels on Behaviors ofCaenorhabditis elegans

Abstract: TRPA and TRPV ion channels are members of the transient receptor potential (TRP) cation channel superfamily, which mediates various sensory transductions. In Caenorhabditis elegans, the TRPV channels are known to affect chemosensation, while the TRPA-1 channel is associated with thermosensation and mechanosensation. We examined thermosensation, chemosensation, and osmosensation in strains lacking TRPA-1 or TRPV channels. We found that TRPV channel knockout worms exhibited similar behavioral deficits associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Thus, these data suggest some overlapping functions of DjTRPAa and DjTRPVab to mediate anandamide-sensing in D. japonica. Similar overlapping or interacting functions of TRPA1 and TRPV1 have previously been suggested in several other systems, including mouse (31), nematodes (58) and the medicinal leech (39).…”
Section: Resultssupporting
confidence: 73%
“…Thus, these data suggest some overlapping functions of DjTRPAa and DjTRPVab to mediate anandamide-sensing in D. japonica. Similar overlapping or interacting functions of TRPA1 and TRPV1 have previously been suggested in several other systems, including mouse (31), nematodes (58) and the medicinal leech (39).…”
Section: Resultssupporting
confidence: 73%
“…Consequently, C. elegans is a commonly used model organism to examine heat avoidance [5,[7][8][9]. Recently, we demonstrated C. elegans ability to avoid noxious heat is strongly associated with the FLP-18/FLP-21/NPR-1 neuropeptide signaling pathways but results also suggested that other neuropeptides signaling pathways or classical neurotransmitters are most likely playing an important role [7].…”
Section: Introductionmentioning
confidence: 96%
“…C. elegans is specifically suitable to study nociception as it exhibits a well-defined and reproducible nocifensive behavior, involving a reversal and change in direction away from the noxious stimulus [5][6][7]. Consequently, C. elegans is a commonly used model organism to examine heat avoidance [5,[7][8][9]. Following the genome sequencing of C. elegans, some genes were classified as Transient Receptor Potential (TRP) ion channel proteins with important sequence homologies to mammalian TRP channels including Transient Receptor Potential Vanilloid Channels (TRPVs) [5].…”
Section: Introductionmentioning
confidence: 99%